2018
DOI: 10.1007/978-3-319-99885-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Difficulty Level in an Infant-Robot Movement Contingency Study

Abstract: This paper presents a personalized contingency feedback adaptation system that aims to encourage infants aged 6 to 8 months to gradually increase the peak acceleration of their leg movements. The ultimate challenge is to determine if a. socially assistive humanoid robot can guide infant learning using contirngent rewards, where the reward threshold is personalized for each infant using a reinforcement learning algorithm. The model learned from the data captured by wearable inertial sensors meMuring infant leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The robotic system's ability to recognize infants' emotions is the leading point for providing effective and spontaneous infant robotic interaction. Indeed, the studies reported in this review demonstrated that the interaction between robots and infants can be greatly useful in healthcare, especially in robotassisted therapies [8,100,107]. Further highlighting the importance of investigating the robot's influence on infants and the infant's affective state during robotic interaction.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The robotic system's ability to recognize infants' emotions is the leading point for providing effective and spontaneous infant robotic interaction. Indeed, the studies reported in this review demonstrated that the interaction between robots and infants can be greatly useful in healthcare, especially in robotassisted therapies [8,100,107]. Further highlighting the importance of investigating the robot's influence on infants and the infant's affective state during robotic interaction.…”
Section: Discussionmentioning
confidence: 86%
“…These findings are indeed based on past infant behavior research that highlighted imitation and contingency learning as two infant behaviors that could be exploited to encourage robot-based motor interventions [99]. Likewise, Pulido et al showed that the robot was able to encourage the infant to reach higher acceleration from their movement to get better rewards from the robot [100]. This finding demonstrated that the robot's physical embodiment and ability to provide various reward types helped it motivate infants and keep their attention for longer than other therapeutic tools.…”
Section: Assistive Robotics For Infantsmentioning
confidence: 76%
“…The high number of initiations by the TR reflects the programming of the robot and is therefore a realistic, ecologically valid measure of how it would operate during any RAIs. The variations in behaviour between the TR and the TD also reflect a benefit of using TRs, in that they can be used in RAI for a longer period of time without compromised welfare of the TAaR and are more contingent on the child's actions and therefore, may reduce frustration and sustain the prolonged attention of the child [52,53]. Thus, in the TR condition these positive participant behaviours were likely reinforced more strongly.…”
Section: Discussionmentioning
confidence: 95%